Assessment of the impact of COVID-19 pandemic on the mental health and wellbeing of pharmacists: A nationwide survey - Erick Wesley Hedima; Roland Nnaemeka Okoro; Gambo Amanda Yelmis; Habiba Adam (Elsevier, 2022)
Objectives: To explore the impact of the COVID-19 pandemic and work on the mental health and wellbeing of pharmacists in Nigeria and investigate the risk of exhaustion, disengagement, burnout, and their associated factors. Methods: This was an online cross-sectional study among pharmacists that involved the use of mental health and wellbeing questionnaire including a 16-item OLBI questionnaire. Descriptive statistical analyses were performed to determine the study distribution. Chi-square test was used to compare categorical variables, while independent sample t-test and one-way ANOVA were used to compare the mean values of two and three groups, respectively. Tukey posthoc test was used to compare various practice settings based on significant factors, while a two-sided Dunnett t-test was used to compare between groups for other significant factors. A p-value less than 0.05 was considered statistically significant. Results: Of the 612 pharmacists invited to participate in the survey, 426 completed and submitted the questionnaire giving a response rate of 69.6%. The Cronbach's alpha for wellness and mental health survey instrument in our study population is 0.74, while the average Cronbach's alpha for a 16-item OLBI questionnaire is 0.62 in our study population. The high risk of exhaustion and disengagement were met by 75.6% and 77.2% of the respondents, respectively. Eighty-three respondents (19.5%) met thresholds for either high risk of exhaustion or disengagement, while 66.2% had both a high risk of exhaustion and disengagement (burnout). Significant proportions of respondents with undergraduate pharmacy degree as the highest qualification obtained (70.6%, p < 0.001), in the hospital practice setting (62.8%, p < 0.001), and in full-time employment type (68.1%, p = 0.004) had the higher risk of burnout compared to their counterparts. Conclusion: The COVID-19 pandemic and work significantly impacted the mental health and wellbeing of a considerable proportion of the respondents. Burnout affects the majority of pharmacists in Nigeria and is linked to undergraduate pharmacy degrees as the highest qualification obtained, hospital practice settings, and full-time employment. Thus, mitigating strategies from employees, government, and organizations are recommended to help improve working conditions and promote the well-being of pharmacists in Nigeria.